“Linguistic autumn”? A remark in connection with Vytautas Kardelis’s article “Three questions regarding the prosodic system of the Lithuanian language” (Lietuvių kalba, 11, 2017) - Andronov, Aleksey; Bakšienė, Rima (Lietuvių kalba, 2018)
Some considerations in connection with the three main claims in Vytautas Kardelis’s article Three questions regarding the prosodic system of the Lithuanian language, concerning (a) the order of procedures in the investigation of the ‘sound form of language’, (b) the domain of prosodic features and (c) the term priegaidė. According to Kardelis, the description of speech chain should begin with an instrumental investigation. This may be true of acoustic analysis of a signal (not necessarily that of speech), but not the phonological analysis of a speech chain that, by definition, begins with isolating its discrete units, which, at the same time, are the units of the phonological system of the language in question. Likewise, phonetic suprasegmental elements (pitch, tone, etc.) may be associated with any loci of speech chain, including those coinciding with individual phonemes, either vowel or consonantal, but the domain of prosodic features, such as acute and circumflex in Lithuanian, is undoubtedly the syllable, rather than separate phonemes. In poliaccentual languages, syllable accents can be absolutely adequately described using the term priegaidė, which here means ‘syllable intonation’, while substituting it with ‘tone’ or ‘stress’ is misleading and, in the last analysis, simply fruitless or simply wrong.
Keywords: none